The safety and immunogenicity of a bivalent conjugate vaccine against Salmonella enterica Typhi and Paratyphi A in healthy Indian adults: a phase 1, randomised, active-controlled, double-blind trial - Kulkarni, PS; Potey, AV; Bharati, S; Kunhihitlu, A; Narasimha, B; Yallapa, S; Dharmadhikari, A; Gavade, V; Kamat, CD; Mallya, A; Sarma, AD; Goel, S; et al. (Elsevier, 2024)
Background Enteric fever caused by Salmonella enterica Typhi and Salmonella Paratyphi A is an important public health problem, especially in low-income and middle-income countries with limited access to safe water and sanitation. We present results from, to our knowledge, the first ever human study of a bivalent paratyphoid A-typhoid conjugate vaccine (Sii-PTCV).